LINGUISTIC LANDSCAPE ON THE MENU LIST OF JAPANESE RESTAURANT IN PADANG CITY: LANSKAP LINGUISTIK PADA DAFTAR MENU RESTORAN ALA JEPANG DI KOTA PADANG - Muhammad Rizki Pratama; Diana Kartika; Oslan Amril; Syahrial Syahrial (LLDIKTI Wilayah X, 2023)
This research aims to describe the form and function of Linguistic Landscape on the menu list display in the selected research object. This research uses descriptive qualitative method with analysis of language code types using the theory of Landry and Bourhis who analyse the form of language code types in the Linguistic Landscape. The data in this study is in the form of a collection of menu lists in Japanese-style restaurants that have been determined and taken by taking pictures via mobile phones. The results of this study show that the information obtained from the menu list in the specified Japanese-style restaurants such as Ichiban Sushi, Decoboco, Ramen 1, Sushi Rock n Roll and Aotori uses several languages namely Indonesian, English, Japanese, Chinese, and Thai. The overall data pertaining to the Japanese language in them is 259 data. The language is displayed monolingually with a total of 92 data, bilingual with a total of 157 data, and multilingual with 10 data. The use of Indonesian symbolises the identity of the National language, as a preference, priority and language preservation, while the use of English because it is an international language that cannot be separated from its role as a tourism language that is able to support attractiveness and has an effect on the economy, as well as Japanese as a sign of national characteristics and identity in language preservation so as not to get out of its authenticity zone. The function of Linguistic Landscape found in this research is in the form of an informative function that puts forward the characteristics and identity of the region and a symbolic function that explains the meaning of symbols that exist in an area around the marker in Linguistic Landscape.